2020
DOI: 10.20870/oeno-one.2020.54.1.2458
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the three main genetic backgrounds of grapevine rootstocks on petiolar nutrient concentrations of the scion, with a focus on phosphorus

Abstract: Background and aims: In most viticultural areas of the world, Vitis vinifera grapevines require grafting onto phylloxera-tolerant rootstocks of American origin. The species most commonly used in rootstock creation are Vitis berlandieri, V. riparia and V. rupestris. Rootstocks not only provide tolerance to phylloxera but also ensure the supply of water and mineral nutrients to the scion. The aim of the study was to investigate the extent to which rootstocks with different genetic backgrounds modify the mineral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 29 publications
1
53
0
Order By: Relevance
“…Additionally, the alcohol content and total dry extract were statistically higher in the wines of Semester 2. According to some authors, rootstocks may differ in their ability to take up potassium, and they can influence grape and wine mineral composition (Gautier et al, 2020;Miele and Rizzon, 2017;Kodur, 2011).…”
Section: Classical Analysis Of the Winesmentioning
confidence: 99%
“…Additionally, the alcohol content and total dry extract were statistically higher in the wines of Semester 2. According to some authors, rootstocks may differ in their ability to take up potassium, and they can influence grape and wine mineral composition (Gautier et al, 2020;Miele and Rizzon, 2017;Kodur, 2011).…”
Section: Classical Analysis Of the Winesmentioning
confidence: 99%
“…Today more than 80% of vineyards employ grafting [36]. Previous research on grafted grapevines has shown that rootstock genotypes influence scion phenotypes such as leaf ionomic profiles [37,38], shoot gene expression [39], and leaf morphology [40]. Interestingly, grapevine rootstock genotypes have distinct bacterial rhizosphere communities [41,42], and the influence of rootstock genotype on root-associated microbiota appears to increase with vine age [43].…”
Section: Introductionmentioning
confidence: 99%
“…Today more than 80% of vineyards employ grafting (Ollat et al 2016). Previous research on grafted grapevines has shown that rootstock genotypes influence scion phenotypes such as leaf ionomic profiles (Lecourt et al 2015;Gautier et al 2020), shoot gene expression (Cookson and Ollat 2013), and leaf morphology (Migicovsky et al 2019). Interestingly, grapevine rootstock genotypes have distinct bacterial rhizosphere communities (D'Amico et al 2018;Marasco et al 2018), and the influence of rootstock genotype on root-associated microbiota appears to increase with vine age (Berlanas et al 2019).…”
Section: Introductionmentioning
confidence: 99%